FACTORS CONTRIBUTING TO CHILD STUNTING IN NIGERIA: A HOLISTIC EXAMINATION OF SOCIOECONOMIC DISPARITIES AND MATERNAL EDUCATION - Smith, Emily; Brown, Sarah; Adebayo , Ogunwale (Global Journal of Medical and Health Science, 2023)
Child stunting remains a critical public health concern in Nigeria, with far-reaching implications for development, productivity, and overall well-being. This study utilizes data from the 2018 Nigeria Demographic and Health Survey to comprehensively examine factors contributing to child stunting in Ogun State, Nigeria. The prevalence of stunting among children under the age of five in this region is estimated at 23%, classified as medium according to WHO standards. Notably, age emerges as a significant predictor of stunting, with children aged 36 months and older at the highest risk. Surprisingly, sex, maternal education, household income, and residence type do not exhibit significant associations with stunting in this population. These findings underscore the importance of targeted nutritional interventions, with a focus on children aged 3-4 years, to mitigate the prevalence of stunting. Moreover, the relatively lower prevalence of stunting in Ogun State compared to the national average suggests potential regional disparities and the influence of socioeconomic factors. As maternal education and household income do not show direct correlations with stunting, future research should explore the nuanced interplay between these factors and childhood malnutrition in Nigeria. This study contributes valuable insights into the multifaceted nature of child stunting in Nigeria, highlighting the need for holistic approaches that address both regional and age-specific disparities.